EIF4A3-induced circ_0022382 promotes breast cancer cell progression through the let-7a-5p/PI3K/AKT/mTOR signaling pathway and SLC7A11 axis - Liu, Wei; Zhang, Jun; Zhang, Jiawen; Ye, Yu; Zhu, Jianqin; Yu, Qiwen; Li, Tao; Sun, Xiaochun; Chen, Huabiao (Frontiers in Oncology, 2025)
IntroductionBreast cancer is one of the most common cancers in women and poses a serious threat to women's health. Circular RNAs (circRNAs) have been found to be specifically expressed in cancers and regulate the growth and death of tumor cells. The role of circRNAs in breast cancer remain unknown. In this study, we explored the impacts of circRNAs on the progression of breast cancer cells.MethodsUsing bioinformatics analysis, we screened out one up-regulated circRNA in breast cancer, and its function and regulatory mechanisms were confirmed by quantitative real-time PCR, cell counting kit-8 experiment, migration assay, dual luciferase reporter assay, Kyoto Encyclopedia of Genes and Genomes enrichment analysis, cell immunofluorescence, clone formation assay, scratch wound healing experiment, RNA immunoprecipitation and subcutaneous tumor-bearing experiments.ResultsCirc_0022382 was highly expressed in breast cancer cell lines MDA-MB-231, MCF-7 as well as breast cancer tissues, and promoted the proliferative and migratory capacity of breast cancer cells. In terms of regulatory mechanisms, circ_0022382 activated PI3K/AKT/mTOR signaling pathway and SLC7A11 by sponging let-7a-5p, while knockdown of circ_0022382 contributed to the occurrence of disulfidptosis. In addition, EIF4A3 promoted the expression of circ_0022382 in MDA-MB-231 and MCF-7. Consistently, knockdown of circ_0022382 inhibited the growth of breast cancer cells in vivo.DiscussionCirc_0022382 and its related molecules may be effective targets for diagnosis or targeted therapy of breast cancer.